Probing intercultural competence in Malaysia: a relational framework - Dalib, Syarizan (EDP Sciences, 2017)
Studies in intercultural competence are quite numerous but they were mainly derived from Eurocentric experiences.Since Eurocentric scholars may become oblivious to certain elements or issues of intercultural communication that are pertinent to Asian people, the Western conception of intercultural competence have been argued for its relevance in the Asian world.This paper aims to revisit the current (Eurocentric) perspective of intercultural competence and probes an alternative perspective of intercultural competence by reviewing current Asian literature. Our review suggests that the conception intercultural competence must consider relational aspects when it is situated within Asian experiences.Since relational aspects were a noted gap in the existing Eurocentric definitions, this paper proposes a relational framework in probing intercultural competence in Malaysia.